HOTS-Oriented Thematic RPP Learning: Increasing the Independence of Elementary School Students - Rohmah, Ismu Musi'atu; Sutama (Universitas Pendidikan Ganesha, 2023)
The teacher before carrying out the teaching and learning process must make a learning implementation plan (RPP). Making lesson plans before the teaching process is very important because it serves as a teacher's guide in carrying out learning in the classroom. There are still teacher problems in preparing lesson plans. The study aims to develop a HOTS-oriented thematic learning implementation plan (RPP) is to increase the main values of strengthening character education (PPK) for class IV students. This study used an experimental group of 10 students related to the implementation of HOTS-oriented thematic lesson plans in increasing student independence. Interviews, observations, and written documentation are the three primary methods of data gathering used in this investigation. Both qualitative and quantitative methods of data analysis are used in this process. The results of this study explain that the application of HOTS-oriented thematic lesson plans is proven to be able to significantly increase student independence. The advice that can be conveyed from the results of this study is the need for teacher support in planning, implementing, and evaluating the application of HOTS-oriented thematic lesson plans. Considering that this research was only carried out in an effort to increase student independence, future research can apply HOTS-oriented thematic lesson plans aimed at increasing learning achievement or other abilities in students.